Ownership structure and capital structure interaction: evidence from sri lankan panel data - Gunathilaka, C. (University of Jaffna, 2012)
The study examines the interaction of capital structure and ownership structure using a sample of sixty five (65) firms listed in the Colombo Stock Exchange. Equity block holders are identified and grouped as ‘Parent company’, ‘other Institutional shareholders’ and ‘Managers’. Generalized Method of Moments (GMM) estimator is employed for an unbalanced panel data for years, from 2006 to 2010. The dynamic tests reveal that there is a significant negative influence of profitability, asset structure, and operating risk on the debt ratio of firms. Growth is insignificant and affects negatively to leverage. The size has a significant positive impact on financial leverage. The institutional ownership and managerial ownership is negatively related to the leverage while ownership concentration with a parent company positively affects the leverage. This suggests that concentrated ownership and high debt level together causes high risk for firms. Hence, the firms would prefer a lower debt ratio as means of risk reduction. In contrast, the parent company ownership does not raise risk and therefore firms prefer higher debt level. Further the institutional investors seek low geared firms in reducing the risk of investment. The findings also indicate that the large firms have easy access to the credit market and become more levered. The firms use retained earnings largely, hence the increased revenue results in low debt ratio. The results also indicate an application of pecking order theory for finance and that the institutional investors are seeking for low geared firms. Hence the firms are subject to the control by market forces.
Keywords: Capital structure; Ownership structure; Dynamic panel data